Lectotypification of three Linnaean names in Impatiens (Balsaminaceae) - Singh, Rajeev Kumar (Phytotaxa, 2017)
The genus Impatiens Linnaeus (1753: 937) consists of about 1000 species, distributed in the tropical and subtropical regions of the Old World as well as in the northern temperate regions (Mabberley 2008). In India there are about 215 species of Impatiens recorded so far, of which 142 species are endemic, and the highest diversity occurs in two regions, viz. the Eastern Himalayas and the Western Ghats (Singh 2016a, 2016b, Singh & Garg 2016). During an ongoing study on the systematics of Impatiens in India, a total of 37 binomials have already been lectotypified and one neotypified previously (Singh 2016a, 2016b). Linnaeus (1753) published 7 names under Impatiens [Impatiens balsamina Linnaeus (1753: 938), I chinensis Linnaeus (1753: 937), I. cornuta Linnaeus (1753: 937), I. latifolia Linnaeus (1753: 937), I. oppositifolia Linnaeus (1753: 937), I. triflora Linnaeus (1753: 938) and I. noli-tangere Linnaeus (1753: 938)] in Species Plantarum. The names I. chinensis, I. cornuta and I. latifolia appear to be yet untypified and are investigated here as a part of systematic study of this genus in India. The designation of the nomenclatural type for these names is based on an assessment of Linnaeus’s original materials and the literature cited in protologue. The images of the selected lectotypes specimens at BM and LINN are available online (http://www.nhm.ac.uk/research-curation/scientific-resources/collections/botanical-collections and http://linnean-online.org/linnaean_herbarium.html).